Acceptance-Rejection Sampling Based Monte Carlo Ray Tracing in Anisotropic Porous Media. (15th May 2020) - Wang, P.; Li, J.B.; Zhou, L.; Liu, D.Y.
Abstract: In this paper, a Monte Carlo ray-tracing method for modeling the incident irradiation propagation in a porous absorber with linear variable pore structure is presented. An acceptance-rejection method (ARM) is employed to generate each step size of the photon's free path according to the specific radiative characteristics of the anisotropic porous medium. The method we proposed overcomes the limitation of the inverse transform method (ITM) by avoiding the integration process to obtain the cumulative distribution function. Using this method, the volumetric distribution in an absorber with a linear variable pore structure is determined. Three typical linear pore structure layouts—increasing (I-type), decreasing (D-type), and constant (C-type)—are analyzed. In general, the D-type layout achieves excellent optical efficiency and homogeneity of solar irradiation distribution. A sparse porous structure is beneficial for the in-depth propagation of photons, but it also increases the probability of photons scattering out of the medium. Therefore, increasing the density at the backside to intercept the ray effectively improves the optical efficiency. The model developed in this work is useful for understanding the propagation of solar irradiation distribution in a porous absorber with an anisotropic media, which is important for the thermal design of volumetric receivers. Highlights: Irradiation propagation is modeled based on MCRT in an anisotropic porous absorber. Acceptance–rejection method (ARM) is employed to generate the photon's free path. Method overcomes the limitation of the inverse transform method (ITM) and more adaptable. Solar irradiation absorption optimization is achieved using an anisotropic porous structure.